HISTORY OF AFRICA AND THE AFRICAN BRAZILIAN SCHOOL: MYTH OR REALITY? - Raquel Amorim dos Santos; Wilma de Nazaré Baía Coelho (Editora da Universidade de Santa Cruz do Sul, 2013)
This study is subject to Social Representations and Race Relations. It analyzes the social representations of teachers about race relations in the curriculum of elementary school. This research was based on theoretical and methodological Moscovici (1978) and Jodelet (2001), Gomes (1995, 2006), Coelho (2009) and Gomes and Silva (2006), for the analysis of social representations, with the first and with others on training and race relations. The study is a descriptive type. Used as a tool for collecting data: official documents, questionnaires and focus groups. We infer that racial prejudice is presented implicitly, in Brazilian society, which contributes to the dissemination and ratification of racism and discrimination in various social sectors, including the school. We conclude that the initial teacher training and continuous is a crucial time for the formulation of a pedagogy that works with cultural diversity. The absence of such training is critical for its subversion of stereotypes and discriminatory practices crystallized in relation to black at school and in their didactic and pedagogical tools.